PURIFICATION, CHARACTERIZATION, AND EVALUATION OF FIBRINOLYTIC ACTIVITY OF STAPHYLOKINASE FROM LOCALLY ISOLATED STAPHYLOCOCCUS AUREUS GH38 - & Aziz, Noori (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to purify, characteristic, and fibrinolytic activity of staphylokinase (SAK), is an enzyme activates plasminogen to form plasmin, which digest fibrin clots that cause thrombosis clot. Staphylokinase was purified from local isolate Staphylococcus aureus GH38 by ammonium sulfate precipitation at 70% saturation followed by ion exchange chromatography (CM-Cellulose) with a purification fold 2.73, and 1.53, and recovery 72.1, and 33.11% in wash and elution steps respectively. The partially purified enzyme was high activity at 40°C with pH 7 and the enzyme retained 100% of its activity at 35°C with pH 7. The activity of an enzyme increased by its treatment with calcium and sodium chloride, while the activity affected when incubated with mercury, silver, and iron chloride. The enzyme have high effective against thrombus (blood clot), which encourage the use of enzyme in the treatment as therapeutic agent to remove clots formed in the human body.